Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1103/physrevd.74.045032
|View full text |Cite
|
Sign up to set email alerts
|

Semiclassical approach to the decay of protons in circular motion under the influence of gravitational fields

Abstract: We investigate the possible decay of protons in geodesic circular motion around neutral compact objects. Weak and strong decay rates and the associated emitted powers are calculated using a semiclassical approach. Our results are discussed with respect to distinct ones in the literature, which consider the decay of accelerated protons in electromagnetic fields. A number of consistency checks are presented along the paper.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…where p 1 and p 2 are the source particles, described by a classical current corresponding to the states of a two level system following a prescribed classical trajectory with proper acceleration a, and q i are the emitted particles, described by quantized fields. (For further details, see [5,6], for instance.) We assume that the respective masses m qi of the emitted particles q i obeys m qi < m p1,2 , where m p1 and m p2 stands for, respectively, the masses of the source particles p 1 and p 2 .…”
Section: The Semi-classical Formalismmentioning
confidence: 99%
See 3 more Smart Citations
“…where p 1 and p 2 are the source particles, described by a classical current corresponding to the states of a two level system following a prescribed classical trajectory with proper acceleration a, and q i are the emitted particles, described by quantized fields. (For further details, see [5,6], for instance.) We assume that the respective masses m qi of the emitted particles q i obeys m qi < m p1,2 , where m p1 and m p2 stands for, respectively, the masses of the source particles p 1 and p 2 .…”
Section: The Semi-classical Formalismmentioning
confidence: 99%
“…If m p1 < m p2 + i m qi , the process is known to be forbidden for inertial trajectories (a = 0). It is intuitive to expect that, if the source is supposed to follow a prescribed trajectory, the momentum k i of the emitted particle q i , measured in the rest frame of the source, must be constrained to |k i | ≪ m 1,2 [5,6]. Moreover, the mean energyω i of the emitted particles (also measured in the proton's reference frame) is of the order of the source proper acceleration [5], i.e.,ω…”
Section: The Semi-classical Formalismmentioning
confidence: 99%
See 2 more Smart Citations
“…This experiment is cited in standard textbooks, see for example [2], as the evidence for the ideal clock hypothesis. Even if clocks can be considered ideal under the regime in which particle accelerators normally operate, more generally, it has been proven by several authors that this is not the case [3][4][5][6]. They have studied the decay law of different particles, in rectilinear and circular motion, as a function of the proper acceleration a and they have shown that the rate depends on the particle trajectory.…”
Section: Introductionmentioning
confidence: 99%